1989
DOI: 10.1007/bf02030078
|View full text |Cite
|
Sign up to set email alerts
|

Infra-red surface thermography. Evaluation of a new radiometry instrument for measuring skin temperature over joints

Abstract: A study is reported of the evaluation of a new portable, light-weight, infrared thermometer, for the measurement of the skin temperature over joints. A high degree of reproducibility was observed, but no increase in heat was found over selected rheumatoid joints. The instrument will prove useful in detecting temperature changes in disease states where the changes are considerable, and where the ambient temperature can be strictly controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…IRT has been successfully used in the diagnosis and assessment of recovery after treatment in Raynaud's phenomena [52,[172][173][174], gout [175] and arthritis [176,177]. Arnold et al reported that, IRT is an excellent technique for measurement of skin temperature over different joints [178]. Ring demonstrated that, the subjects suffering from rheumatoid arthritis, juvenile arthritis, osteoarthrosis, gout, etc.…”
Section: Diagnosis Of Rheumatic Diseasesmentioning
confidence: 99%
“…IRT has been successfully used in the diagnosis and assessment of recovery after treatment in Raynaud's phenomena [52,[172][173][174], gout [175] and arthritis [176,177]. Arnold et al reported that, IRT is an excellent technique for measurement of skin temperature over different joints [178]. Ring demonstrated that, the subjects suffering from rheumatoid arthritis, juvenile arthritis, osteoarthrosis, gout, etc.…”
Section: Diagnosis Of Rheumatic Diseasesmentioning
confidence: 99%